The Other Dead. An Ethnohistorical Approach to Religious Diversity in the Spanish Cemeteries - Tarrés, Sol; Solé Arraràs, Ariadna; Moreras, Jordi (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2018)
Cemeteries become social spaces where many symbolic meanings converge both in their material and immaterial dimensions, and perhaps above all, in their expression of communities and their construction of identities and otherness. This article explores how religious diversity has found its place within Spanish cemeteries. Although this debate is linked to contemporary immigration and the religious groups it has brought, religious diversity has challenged Spanish funerary customs for a long time. As we will argue in this article, the debates around where to put the “other dead” are an inherent part of funerary heritage in Spain. By looking at four spaces dedicated to the burial of non-Catholics who died in Spain, we will attempt to show how some symbolic and identity-based constants related to the separation of graves persist today and how Spanish society is opening up to considering burial spaces as part of a common heritage.